2002
DOI: 10.1002/app.10339.abs
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and flocculation properties of poly(diallyldimethyl ammonium chloride–vinyl trimethoxysilane) and poly(diallyldimethyl ammonium chloride–acrylamide–vinyl trimethoxysilane)

Abstract: Poly(diallyldimethyl ammonium chloride-vinyl trimethoxysilane) [P(DAD-MAC-VTMS)] and poly(diallyldimethyl ammonium chloride-acrylamide-vinyl trimethoxysilane) [P(DADMAC-AM-VTMS)], the latter a new cationically charged and hydrophobically modified flocculant, were obtained by radical polymerization initiated by potassium persulfate. The effects of the vinyl trimethoxysilane (VTMS) feed ratio on the intrinsic viscosity and solubility of the polymers were examined. The effects of the flocculants on turbidity remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…However, from Table 1, it is found that the yield of ADA is not improved with an increase of the reaction temperature, especially all these yields at different temperatures are lower than 60%, though the reaction time at the optimum point can be reduced with increasing reaction temperature. The cause is that with increasing reaction temperature by conditional heating, reaction rates of side reaction and the quaterization reaction are more obviously accelerated than reaction rate of forming ADA (Boothe, 1969;Hunter, 1979;Zhao et al, 2002). Table 2 illustrates different yields of ADA by MI, UI and conventional heating at low temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from Table 1, it is found that the yield of ADA is not improved with an increase of the reaction temperature, especially all these yields at different temperatures are lower than 60%, though the reaction time at the optimum point can be reduced with increasing reaction temperature. The cause is that with increasing reaction temperature by conditional heating, reaction rates of side reaction and the quaterization reaction are more obviously accelerated than reaction rate of forming ADA (Boothe, 1969;Hunter, 1979;Zhao et al, 2002). Table 2 illustrates different yields of ADA by MI, UI and conventional heating at low temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In reference to the literatures (Wandrey et al, 1999; Brain, 1995;Butler and Angelo, 1958;Butler and Bunch, 1949;Negi et al, 1967) as well as our previous works (Zhao et al, 2002;Chang et al, 2000), synthesis of ADA is a key step for producing higher molecular weight polymers of DADMAC (PDADMAC) as a flocculant. In the conventional methods, the yields of ADA at both high temperature and low temperature are too low and reaction time is long so that yield of high-purity DADMAC is lower than 57% and reaction time is longer than 6 h. This problem seriously inhibits the application of higher molecular weight polymer of DADMAC as a highly efficient flocculant.…”
Section: Introductionmentioning
confidence: 90%
“…The micrographs proved that some hydrophobic groups in polymer molecule are helpful to enlarge molecule. This may be resulted from the self-forming behavior of the molecules which is associated in the manner of micelle [7]. At the same time, there is repulsive force among the hydrophobic groups, which prevents the molecular chain bonding together.…”
Section: Tem Imagesmentioning
confidence: 99%
“…In the past few decades, researchers have found hydrophobically modified polymers showed excellent properties in the oily wastewater treatment in oil recovery operations and were effective in cleaning up organic contaminants in wastewater. These polymers include hydrophobically associating polyacrylate [5,6], vinyl trimethyloxysilane (VTMS) modified PDADMAC [7], hydrophobically modified chitosan [8], hydrophobically modified polycations [9], etc. By introducing hydrophobic group into polymer molecular structure, flocculation performance of the polymer is improved.…”
Section: Introductionmentioning
confidence: 99%
“…However, comparing with other polymer flocculants, PDADMAC is difficult to have high molecular weight, which will make against "adsorption bridging action" of PDADMAC when it is used as a flocculant in water treatment [5,6]. To improve "adsorption bridging action" or reduce the running costs of the PDADMAC flocculants, some modification techniques and preparation methods such as copolymerization with hydrophobic and hydrophilic monomers [7,8], polyelectrolyte complexes (PECs) formed between oppositely charged macromolecules [3,9] and cationic particles prepared by polymer being adsorbed or grafted on clay [10,11] have been reported in recent years. But the above methods cannot resolve the key problem of PDADMAC flocculants as cationic polymer flocculants, which are hoped to have both high molecular weight and high cationic density, namely, have both stronger "adsorption charge neutralization action" and stronger "adsorption bridging action".…”
Section: Introductionmentioning
confidence: 99%